Effect of spraying with Moringa plant extract and potassium silicate on some vegetative growth indicators of banana seedlings obtained from tissue culture Musa spp - Riyadh Mhawesh Al-Muhe; Mahmmod S. Abdul-Wahid (University of Thi-Qar Journal of agricultural research, 2023)
The field experiment was conducted in one of the covered greenhouses in Al-Saran affiliated with the College of Agriculture and Marshes, University of Dhi Qar for the 2022-2023 growing season on banana seedlings of the Grand Nine variety resulting from tissue culture in order to determine the effect of Moringa extract and potassium silicate on the vegetative growth characteristics on 2/5/2023. Aged 3 to 4 months, 48 identical offspring were chosen. First, spraying with Moringa leaves extract at four concentrations (0, 5, 10, and 15) g L-1; second, spraying with potassium silicate at four concentrations (0, 1, 2, and 3) ml L-1. The statistical analysis revealed that Moringa extract at a concentration of 15 g L-1 was superior in terms of all vegetative growth characteristics (plant height (104.38 cm), stem diameter (71.60 mm), number of leaves (10.60), plant leaf-1, and leaf area (1,535.05 square millimeters). cm2, the wet weight of the shoot is (1084.3) g, the dry weight is (120.45 g), and the rate of root propagation is (9.65) g per square centimeter per day. 2 kg-1. The results of the statistical analysis demonstrated the superiority of potassium silicate at a concentration of 3 ml L-1 in all vegetative growth characteristics (plant height (95.90) cm, stem diameter (67.08) mm, number of leaves (9.28) plant leaf-1, leaf area (1,368.0) cm2, and plant weight (13,680.00 g)). The wet weight of the shoot is (943.9) g, its dry weight is (104.14 g), and its rate of root propagation is (9.71) g.2 kg-1, As for the combinations, the combination of Mornica extract and potassium silicate at a concentration of (15 g L-1 x 3 ml L-1) performed the best in terms of vegetative characteristics, plant height (125.67 cm), stem diameter (84.80 mm), and number of leaves (13.40). -1, leaf area (1912.22 cm2), shoot wet weight (1417.5) g, shoot dry weight (157.5) g, and root spread rate (11.4) g 2 kg-1.